Transversality conditions in optimum growth models with or without discounting - Dasgupta, Swapan (Estudios de Economía, 2016)
In the literature on price characterization of optimal paths in stationary models of optimal growth, distinct “transversality conditions” have been pr esented, depending on whether or not utilities are discounted. In the discounted case, this condition takes the form that asymptotically the presente-value prices converge to zero. In the undiscounted case, however, it is of the form that the present value prices are bounded above along the path. It is shown here that under assumptions that are fairly standard in such problems, this difference is superfluous and the same transversality condition characterizes optimal paths in both the discounted and undiscounted cases.